Coping and care-related stress in parents of a child with autism spectrum disorder. Issue 3 (4th May 2018) - Shepherd, Daniel; Landon, Jason; Taylor, Steve; Goedeke, Sonja
ABSTRACT: Background and Objectives: Parenting a child with Autism Spectrum Disorder (ASD) is challenging and can result in elevated levels of parenting stress. This study investigated the relationship between parent-ratings of their child's ASD symptoms and two conceptually different measures of parenting stress: One specific to the ASD context and the other a general stress measure applicable to the broader caregiving context. Additionally, the influence of coping style on the relationship between child's ASD symptoms and parenting stress was investigated. Design and Methods: Using an internet survey, parents ( N = 178) caring for a child with ASD reported on coping strategies, completed two measures of parenting stress, and assessed their child's ASD symptoms. Results: Parenting stress increased with severity of the child's ASD symptoms, but the strength of this relationship depended on whether a general or disorder-specific measure of parenting stress was used. Regression analyses indicated that some coping strategies moderated the impact of ASD symptom severity on the parent's care-related stress, but moderation depended on how stress was conceptualized. Conclusion: This study reinforces the importance of identifying the coping strategies of parents of children with developmental disorders, and highlights the consequences of using different conceptual approaches to measure parenting stress.